Dermoscopy, with and without visual inspection, for the diagnosis of melanoma in adults - Dinnes, Jacqueline; Deeks, Jonathan J.; Chuchu, Naomi; Ferrante di Ruffano, Lavinia; Matin, Rubeta N.; Thomson, David R.; Wong, Kai Yuen; Aldridge, Roger Benjamin; Abbott, Rachel; Fawzy, Monica; Bayliss, Susan E.; Grainge, Matthew J.; et al. (Wiley, 2018)
Background: Melanoma has one of the fastest rising incidence rates of any cancer. It accounts for a small percentage of skin cancer cases but is responsible for the majority of skin cancer deaths. Although history-taking and visual inspection of a suspicious lesion by a clinician are usually the first in a series of ‘tests’ to diagnose skin cancer, dermoscopy has become an important tool to assist diagnosis by specialist clinicians and is increasingly used in primary care settings. Dermoscopy is a magnification technique using visible light that allows more detailed examination of the skin compared to examination by the naked eye alone. Establishing the additive value of dermoscopy over and above visual inspection alone across a range of observers and settings is critical to understanding its contribution for the diagnosis of melanoma and to future understanding of the potential role of the growing number of other highresolution image analysis techniques. Objectives: To determine the diagnostic accuracy of dermoscopy for the detection of cutaneous invasive melanoma and atypical intraepidermal melanocytic variants in adults, and to compare its accuracy with that of visual inspection alone. Studies were separated according to whether the diagnosis was recorded face-to-face (in-person) or based on remote (image-based) assessment. Search methods: We undertook a comprehensive search of the following databases from inception up to August 2016: Cochrane Central Register of Controlled Trials; MEDLINE; Embase; CINAHL; CPCI; Zetoc; Science Citation Index; US National Institutes of Health Ongoing Trials Register; NIHR Clinical Research Network Portfolio Database; and the World Health Organization International Clinical Trials Registry Platform. We studied reference lists and published systematic review articles. Selection criteria: Studies of any design that evaluated dermoscopy in adults with lesions suspicious for melanoma, compared with a reference standard of either histological confirmation or clinical follow-up. Data on the accuracy of visual inspection, to allow comparisons of tests, was included only if reported in the included studies of dermoscopy. Data collection and analysis: Two review authors independently extracted all data using a standardised data extraction and quality assessment form (based on QUADAS-2). We contacted authors of included studies where information related to the target condition or diagnostic threshold were missing. We estimated accuracy using hierarchical summary ROC methods. Analysis of studies allowing direct comparison between tests was undertaken. To facilitate interpretation of results, we computed values of sensitivity at the point on the SROC curve with 80% fixed specificity and values of specificity with 80% fixed sensitivity. We investigated the impact of in-person test interpretation; use of a purposely developed algorithm to assist diagnosis; observer expertise; and dermoscopy training. Main results: A total of 104 study publications reporting on 103 study cohorts with 42,788 lesions (including 5700 cases) were included, providing 354 datasets for dermoscopy. The risk of bias was mainly low for the index test and reference standard domains and mainly high or unclear for participant selection and participant flow. Concerns regarding the applicability of study findings were largely scored as ‘High’ concern in three of four domains assessed. Selective participant recruitment, lack of reproducibility of diagnostic thresholds and lack of detail on observer expertise were particularly problematic. The accuracy of dermoscopy for the detection of invasive melanoma or atypical intraepidermal melanocytic variants was reported in 86 datasets; 26 for evaluations conducted in-person (dermoscopy added to visual inspection) and 60 for image-based evaluations (diagnosis based on interpretation of dermoscopic images). Analyses of studies by prior testing revealed no obvious effect on accuracy; analyses were hampered by the lack of studies in primary care, lack of relevant information and the restricted inclusion of lesions selected for biopsy or excision. Accuracy was higher for in-person diagnosis compared to image-based evaluations (relative diagnostic odds ratio (RDOR) of 4.6; 95% CI 2.4, 9.0, P<0.001). Accuracy was compared for (a) in-person evaluations of dermoscopy (26 evaluations; 23,169 lesions and 1664 melanomas) versus visual inspection alone (13 evaluations; 6740 lesions and 459 melanomas) and for (b) image-based evaluations of dermoscopy (60 evaluations; 13,475 lesions and 2851 melanomas) versus image-based visual inspection (11 evaluations; 1740 lesions and 305 melanomas). For both comparisons, meta-analysis found dermoscopy to be more accurate than visual inspection alone, with RDORs of (a) 4.7 (95% CI: 3.0 to 7.5; P < 0.001) and (b) 5.6 (95% CI: 3.7 to 8.5; P < 0.001). These effects correspond to predicted differences in sensitivity of (a) 16% (95% CI: 8%, 23%) (92% for dermoscopy+visual inspection vs 76% for visual inspection) and (b) 35% (95% CI 24% to 46%) (81% for dermoscopy vs 47% for visual inspection) at a fixed specificity of 80%; and topredicted differences in specificity of (a) 20% (95% CI 7%, 33) (95% for dermoscopy plus visual inspection vs 75% for visual inspection) and (b) 40% (95% CI 27, 57) (82% for dermoscopy vs 42% for visual inspection) at a fixed sensitivity of 80%. Using the median prevalence of disease in each set of studies ((a) 12% for in-person and (b) 24% for image-based) for a hypothetical population of 1000 lesions, an increase in sensitivity of (a) 16% (in-person) and (b) 35% (image-based) from using dermoscopy at a fixed specificity of 80% equates to a reduction in the number of melanomas missed of (a) 19 and (b) 81 with (a) 176 and (b) 152 false positive results. An increase in specificity of (a) 20% (in-person) and (b) 40% (image-based) at a fixed sensitivity of 80% equates to a reduction in the number of unnecessary excisions from using dermoscopy of (a) 176 and (b) 304 with (a) 24 and (b) 48 melanomas missed. The use of a named or published algorithm to assist dermoscopy interpretation (as opposed to no reported algorithm or reported use of pattern analysis) had no significant impact on accuracy either for in-person (RDOR 1.4, 95% CI 0.34, 5.6; P=0.17) or image-based (RDOR 1.4, 95% CI 0.60, 3.3; P=0.22) evaluations. This result was supported by subgroup analysis according to algorithm used. Higher accuracy for observers reported as having high experience and for those classed as ‘expert consultants’ in comparison to those considered to have less experience in dermoscopy was observed, particularly for image-based evaluations. Evidence for the effect of dermoscopy training on test accuracy was very limited but suggested associated improvements in sensitivity. Authors' conclusions: Despite the observed limitations in the evidence base, dermoscopy is a valuable tool to support the visual inspection of a suspicious skin lesion for the detection of melanoma and atypical intraepidermal melanocytic variants, particularly in referred populations and in the hands of experienced users. Data to support its use in primary care is limited however it may assist in triaging suspicious lesions for urgent referral when employed by suitably trained clinicians. Formal algorithms may be of most use for dermoscopy training purposes and for less expert observers, however reliable data comparing approaches using dermoscopy in-person are lacking.